Late folding-related magnetic foliation in the active Ferdows (northeastern Iran) thrust–fold system. (15th August 2015) - Rashid, Hamideh; Cifelli, Francesca; Mattei, Massimo
Highlights: AMS used to solve the ambiguity on the tectonic or sedimentary origin of magnetic lineation. The magnetic lineation in the Ferdows thrust–fold system is tectonically originated. Cryptic cleavage system developed as a consequence of later shortening. AMS is a valuable tool to study recent deformation processes in sedimentary rocks. Abstract: In this work we present new AMS and structural results from the Ferdows active fold–thrust system (Lut block, Central Iran). AMS analyses show that the Miocene units of the Upper Red Formation have a well defined magnetic fabric of tectonic origin, with both magnetic lineation and magnetic foliation oriented parallel to the regional fold axes. In most of the cases the magnetic fabric, acquired when the bedding was still horizontal, is related to different degrees of LPS shortening. In some other cases, the magnetic foliation is vertical and oblique to the bedding, suggesting that in the Ferdows thrust–fold structure a cleavage system, not visible at the outcrop scale, has been developed as a consequence of later shortening related to the activity of the thrust system, responsible of the recent earthquakes in the area. Results from this study establish a relationships between the recent tectonics of the area and the evolution of the magnetic fabric and demonstrate that a well defined magnetic fabric of pure tectonic origin can also develop in poorly deformed rocks lacking field evidence of pervasive internal deformation.